2018
DOI: 10.1161/strokeaha.118.021789
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Therapy, Cerebral Microbleeds, and Intracerebral Hemorrhage

Abstract: Antiplatelet drug use was associated with increased risk of strictly lobar MBs and increased the intracerebral hemorrhage incidence in participants with CMBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 9 publications
3
25
2
1
Order By: Relevance
“…Our study showed that antiplatelet use was associated with presence of CMBs in ischemic stroke patients with AF/RHD. Although controversies existed in the literature (14, 2628), our finding is consistent with three recent meta-analyses, which all showed similar associations in patients with ischemic stroke or TIA (15, 29, 30). Some of the previous studies suggested that different type of antiplatelets may have different effects on development of CMBs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that antiplatelet use was associated with presence of CMBs in ischemic stroke patients with AF/RHD. Although controversies existed in the literature (14, 2628), our finding is consistent with three recent meta-analyses, which all showed similar associations in patients with ischemic stroke or TIA (15, 29, 30). Some of the previous studies suggested that different type of antiplatelets may have different effects on development of CMBs.…”
Section: Discussionsupporting
confidence: 92%
“…Prior use of antiplatelets and especially aspirin were only significantly associated with occurrence of strictly lobar CMBs rather than deep or infratentorial CMBs. Our findings are in line with the Rotterdam Scan Study (31) and the newly published meta-analysis (30). This result may be explained by the different underlying pathophysiologic mechanisms of CMBs in different locations.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3] Some brain imaging features of intracerebral haem orrhage and cerebral small vessel diseases are associ ated with a higher risk of intracerebral haemorrhage recurrence in general, and in people taking antiplatelet therapy. [4][5][6][7][8] For example, the proportional increase in the risk of intracerebral haemorrhage recurrence is up to five times higher after lobar versus nonlobar haemorrhage, 8 up to sixtimes higher with presence versus absence of cerebral microbleeds on MRI, 7 and roughly fourtimes higher with presence versus absence of superficial siderosis on MRI. 6 Consequently, guidelines and opin ions suggest that location of intracerebral haemorrhage and some features of cerebral small vessel diseases can guide therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis on the relationship between antiplatelet therapy and CMBs found that antiplatelet therapy was significantly associated with presence of CMBs in patients with stroke but not in stroke-free individuals [29]. A more recent meta-analysis [30] that included 37 studies did not just clarify the increased risk of CMBs on antiplatelet therapy; moreover, they related their use to the association with strictly lobar microbleeds rather than deep/infratentorial microbleeds.…”
Section: Discussionmentioning
confidence: 99%